The study of SMEs' E-Commerce adoption in Sabah and Sarawak - Tang, Alan Gui Lian; Jaratin Lily; Chew Tze Cheng @ Nur Alesha Chew (Human Resource Management Academic Research Society (HRMARS), 2022)
This study will focus on how e-commerce helps or contribute to Sabah and Sarawak's SMEs. In addition, the research will be conducted using the TOE (Technology–Organisation-Environment) framework. Not only that, this study will collect the questionnaire from the Sabah and Sarawak's SMEs. Due to the lack of study in Sabah and Sarawak, knowledge of e-commerce adoption could be limited. In a nutshell, this research would help better understand e-commerce uptake among SMEs in Sabah and Sarawak. Besides, the findings are helpful for interested parties, such as policymakers, to develop an appropriate mitigation plan to boost e-commerce adoption in Sabah and Sarawak.